PENGARUH PERSEPSI KETERLIBATAN ORANG TUA TERHADAP HASIL BELAJAR EKONOMI SISWA - Mohamad Rafsanjani (JURNAL PENDIDIKAN AKUNTANSI, 2014)
This research aims to testing Eccles hyphothesis (2005 ) that the influence of parental involvement on learning outcomes is mediated by self-concept of students in their academic abilities . The study was conducted on the students of class XI Social SMAN Malang, with 292 as sample. The analysis was conducted using path analysis model causal steps of the Baron and Kenny (1986 ) and Sobel test. The findings in this research suggest that academic self-concept significantly has a function as mediator variable influencing perceptions of parental involvement on student learning outcomes of economy. However, the role of self-concept variable in academic is partial mediation variable meaning variable that mediate only some of the effects of Â the perception of parental involvement on learning outcomes .It shows that not only self-concept in academic that became the mediator variable of influence perceptios of parental involvement on learning outcome, but there are other variables that also mediate the causal relationship of those two variables. Â